Should children with developmental and behavioural problems be routinely screened for lead?. Issue 4 (1st October 2001) - Lewendon, G; Kinra, S; Nelder, R; Cronin, T
Abstract : AIM: To test the hypothesis that children with behavioural and/or developmental problems have significantly higher blood lead concentrations than the general childhood population. METHODS: Blood samples were taken from 69 children with behavioural and/or developmental problems and 136 controls (children admitted for elective day case surgery under general anaesthetic). Blood lead estimations were carried out using graphite furnace atomic absorption RESULTS: Children with behavioural and/or developmental problems had higher lead concentrations than controls, both in terms of their distribution across the group (meangeometric lead concentrations: 40.7 (cases), 29.2 (controls), ratio of the meansgeometric 1.35 (95% CI 1.17, 1.58)) and the proportion of children with lead concentrations above those commonly defined as "toxic"—that is, 100 μg/l (12% (cases), 0.7% (controls); p < 0.001). Multiple linear regression suggested that this difference was not explained by differences in age, sex, or socioeconomic status of the two comparison groups. CONCLUSIONS: Children with behavioural and/or developmental problems are more likely to have significantly higher blood lead concentrations than the general childhood population. Lead, a known and more importantly, a treatable neurotoxin, would further contribute to the impairment suffered by these children. We argue that this group of children should be routinely screened for lead.